2017
DOI: 10.1007/978-1-4939-7253-1_7
|View full text |Cite
|
Sign up to set email alerts
|

Specific and Generic Isolation of Extracellular Vesicles with Magnetic Beads

Abstract: This chapter covers magnetic bead-based isolation and analysis of the smallest members of extracellular vesicles (EVs), the exosomes (30-150 nm), generally regarded to originate from the multivesicular bodies (MVBs). Also included, are descriptions of how to prepare samples prior to isolations. The magnetic bead-based isolation workflow is dramatically shortened both by omitting the pre-enrichment step and providing an option for a very short capture time. Three direct exosome isolation strategies are describe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 12 publications
0
34
0
Order By: Relevance
“…36 Using this approach the authors demonstrated that the principle of size-exclusion using two polycarbonate membranes (with pore sizes of 200 and 30 nm) permitted the concentration of EVs within this size-range and the later study of CD63 expression using ELISA. Urine-derived CD9-positive exosomes have also been isolated using magnetic beads 37 and Gilani et al have also shown that digital flow cytometry can be a good approach for quantifying the expression of markers of interest in urine-derived EVs from renal-injury patients. 38 Besides biofluid-volume, specific methodological parameters need to be optimised during EVs isolation according to their inherent biochemical properties.…”
Section: Reviewmentioning
confidence: 99%
“…36 Using this approach the authors demonstrated that the principle of size-exclusion using two polycarbonate membranes (with pore sizes of 200 and 30 nm) permitted the concentration of EVs within this size-range and the later study of CD63 expression using ELISA. Urine-derived CD9-positive exosomes have also been isolated using magnetic beads 37 and Gilani et al have also shown that digital flow cytometry can be a good approach for quantifying the expression of markers of interest in urine-derived EVs from renal-injury patients. 38 Besides biofluid-volume, specific methodological parameters need to be optimised during EVs isolation according to their inherent biochemical properties.…”
Section: Reviewmentioning
confidence: 99%
“…For example, although immunocapture by immobilised monoclonal antibodies may yield highly purified EV, this isolation method relies on the presence of a capturing antigen [32]. Given the heterogeneity in protein composition of EV from different origins, only subpopulations of EV can be isolated with this approach.…”
Section: Introductionmentioning
confidence: 99%
“…ExoQuick™ is a novel polymer with advantages of convenience and scalable sample capacity, but it is also possible to co‐precipitate contamination like proteins Meanwhile, antibody‐coated magnetic beads method achieves high purity. The biological method uses immobilized antibodies to interact with EVs' membrane‐bound antigens for specific EVs' isolation but is rather costly . Recently, with the development of technology, microfluidics‐based techniques emerged, isolating EVs with specific traits such as size, density, immunoaffinity, acoustic wave, electrophoretic and electromagnetic manipulations.…”
Section: Extracellular Vesiclesmentioning
confidence: 99%